MULTIMEDIA DEVELOPMENT OF TISSUE CULTURE TECHNIQUES IN HIPPEASTRUM - Suwannasri, Pimchanok; Chotikadachanarong, Kittisak; Patcharatanaroach, Sasinipa; Kankhat, Sirikorn; Bungcoment, Malanee (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
The purposes of this research were 1) to develop multimedia of tissue culture techniques in Hippeastrum, 2) to assess the quality of multimedia and 3) to study the satisfaction of using multimedia. The sample group of this research was 341 students from the schools in Chiangmai and Lamphun Province. The research tools were 1) multimedia of tissue culture techniques in Hippeastrum, 2) media quality assessment form, and 3) satisfaction towards media usage assessment form. The results revealed that 1) multimedia development of tissue culture techniques in Hippeastrum used the cartoon characters as storytellers leading to the main content of the tissue culture in Hippeastrum. For techniques and methods of tissue culture in Hippeastrum, the method of using demonstration video by the experts was chosen.2)The result of the assessment on the quality of multimedia of tissue culture techniques in Hippeastrum by three experts was at a good level with the mean of 4.40. 3) The average overall result of assessment of satisfaction towards multimedia usage of 341 users found that the respondents’ satisfaction was at a very high level with the mean of 4.16.